2008
DOI: 10.1021/ic800871r
|View full text |Cite
|
Sign up to set email alerts
|

Topology Analysis and Nonlinear-Optical-Active Properties of Luminescent Metal−Organic Framework Materials Based on Zinc/Lead Isophthalates

Abstract: Two 3D Zn(II) and Pb(II) isophthalates, [Zn(ip)]n (1) and [Pb4(mu4-O)(ip)3(H2O)]n (2) (H2ip = isophthalic acid), have been prepared under hydro(solvo)thermal conditions and characterized by single-crystal X-ray diffraction. The two complexes crystallize in different space groups (P4(3)2(1)2 for 1 and P2(1)/c for 2) and have different bridging modes of the ip ligand. The 3D framework of 1 is constructed by the interconnection of ZnO4 polyhedra via ip ligands, which represents a chiral net with PtS-type topology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(65 citation statements)
references
References 65 publications
6
59
0
Order By: Relevance
“…[1] The design and synthesis of such networks is driven by diverse potential applications in gas storage, [2] catalysis, [3] electrical conductivity, [4] luminescence, [5] magnetism [6] and optics. [7] Hydrogen has enormous potential as a sustainable, clean and efficient fuel. [8] Thus, many industrial economies are investing in the hydrogen economy [9] as a major contribution to sustainability and for use in the clean technologies of the future.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The design and synthesis of such networks is driven by diverse potential applications in gas storage, [2] catalysis, [3] electrical conductivity, [4] luminescence, [5] magnetism [6] and optics. [7] Hydrogen has enormous potential as a sustainable, clean and efficient fuel. [8] Thus, many industrial economies are investing in the hydrogen economy [9] as a major contribution to sustainability and for use in the clean technologies of the future.…”
Section: Introductionmentioning
confidence: 99%
“…The free benzene-1,2,3-tricarboxylic acid ligand displays a fluorescent emission band at 440 nm (λ ex = 330 nm) based on the literature [33]. The observed largely red-shift of complex 1 from the 1,2,3-H 3 btc ligand emission may be assigned to the ligand-to-metal charge-transfer (LMCT) between delocalized π bonds of the 1,2,3-btc carboxylate groups and p orbitals of the Pb(II) centers [20,34].…”
Section: 5 3 )mentioning
confidence: 95%
“…Previous studies have indicated that metal coordination polymers containing lead(II) ions exhibit photoluminescent properties [18][19][20]. Thus, the photoluminescent property of complex 1 in the solid state has been investigated at room temperature.…”
Section: 5 3 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a large number of metal-organic frameworks (MOFs) based on carboxylate ligands design from 1D chains to 3D frameworks with different topologies were constructed from the versatile, rigid monoaromatic polycarboxylate ligands, such as 1,3,5-benzenetricarboxylate, 1,2-benzenebicarboxylate, 1,3-benzenebicarboxylate and 1,4-benzenebicarboxylate, etc. [13][14][15][16] while rigid biphenyl dicarboxylates as organic linkers are less reported [17][18][19]. As a continuation of our work [20,21], we have now undertaken a study of synthesis and X-ray crystal structure dominations of two zinc complexes [Zn(dpa)] n (1) and {[Zn 2 (dpa)(Pbim)(H 2 O) (OH)] •1.5 (H 2 O)} n (2) based on biphenyl-2,4′-dicarboxylic acid (2,4′-dpa) as the first linker ligand.…”
mentioning
confidence: 99%